Survey of Public Needs on The Design of an Integrated Information System Model for Adolescent, Mother, and Child Health - Kostania, Gita; Cahyani, Desy Dwi; Rosmalawati, Ni Wayan Dwi (Al Makki Publisher, 2024)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) in Indonesia are still high, with MMR reaching 305/100,000 live births and IMR at 22.23 per 1,000 live births. Although the government has launched various programs for adolescent, maternal, and child health, there has been no effort to integrate these programs into a comprehensive reproductive health cycle. This study aims to analyze the needs of the community in designing an integrated information system model for adolescent, maternal, and child health. This study used a survey design conducted in Dau, Malang Regency, Indonesia. The population consisted of all women of childbearing age (15-49 years) totaling 945 people, with a sample size of 311 respondents obtained using the Slovin formula. The sampling technique used cluster sampling from 4 RW in Petungsewu Village, and 279 respondents could be processed. The research instrument used a questionnaire, and the data were analyzed quantitatively in the form of frequency distribution. The results of the data analysis showed that the design of the integrated model of adolescent, maternal, and child health has significant potential as the basis for developing an integrated website system. This system not only facilitates comprehensive health education but also strengthens real-time health recording and reporting mechanisms. This study shows that the integration of health education is essential to meet the different information needs of adolescents, mothers, and children. The model successfully identified and categorized these needs, so that the developed website could provide relevant and specific content for each user group.